3D modelling for time-lapse cross-well CSEM monitoring of CO2 injection into brine filled reservoirs - Swanepoel, R.; Harris, Brett; Pethick, Andrew (CSIRO, 2012)
Carbon Dioxide (CO2) sequestration is one proposed solution to the possible detrimental effects of increased CO2 emissions into the Earth’s atmosphere. A proposed method for CO2 sequestration is capture and storage below the earth’s surface in deep saline reservoirs. Australia’s CO2CRC research group is currently trialling this method of CO2 sequestration by injection into the Paaratte formation in the Otway Basin Australia. As CO2 is injected into brackish or saline water saturated sediments it is expected to create a zone of increased electrical resistivity around the injector well. The crosswell controlled-source electromagnetic method may be capable of mapping the movement of injected CO2 as it expands out from the injection interval. We simulate time-lapse in-hole controlled source electromagnetic surveys using expected change in electrical resistivity that might be associated with CO2 injection. We demonstrate that controlled source electromagnetic methods will successfully monitor CO2 injection given; (i) suitable transmitter type and frequency range; (ii) a monitoring well design that can facilitate the electrical methods and (iii) correct monitoring well location relative to the injection well. In particular we find that, because of the large volume of CO2 that would likely be injected during a large sequestration project even relatively small changes of less than 10% in electrical resistivity associated should be readily detectable. We provide images of the time lapse cross well electromagnetic response for an expanding disk representing 0.1 to 10 kilo tonne of CO2.